Quantitative Estimation of Tabletability of Aceclofenac after Incorporation of Titanium Dioxide using Area under the Curve - Nandi, Souvik; Mishra, Satyaki Aparajit; Sahoo, Rudra Narayan; Swain, Rakesh; Mallick, Subrata (Indian Journal of Pharmaceutical Education and Research, 2020)
Background: Tablet manufacturing with direct compression is one of the leading industrial technique that consumes less time, labour and economic also. But the choice of excipients are critical in this case which will allow the drug to get compressed without granulation techniques. Purpose: Aceclofenac is a BCS class II non-steroidal anti-inflammatory drug, which exerts a low oral bioavailability because of low solubility in aqueous medium. The drug also suffers from compressibility and also shows poor tabletibility. Methods: We have attempted to improve tabletability by incorporating titanium dioxide (TiO2) through kneading and solvent evaporation technique. Results: In the FTIR study revealed that NH and Cl aromatic stretching of aceclofenac has been affected significantly due to binding with TiO2. DSC thermogram ascertained the partial amorphization of the drug in the formulations. Evaluated tabletability from the area under the applied pressure vs tensile strength curve (AUTC) of A1T1 has shown a poor value in contrast to other formulations.
Keywords: Aceclofenac; Tabletability; Titanium dioxide; Direct compression; Area under; the curve